Puerarin offsets the anticoagulation effect of warfarin in rats by inducing rCyps, upregulating vitamin K epoxide reductase and inhibiting thrombomodulin. (January 2017) - Ge, Beikang; Zhang, Zhen; Lam, Teddy Taining; Zuo, Zhong
Abstract: Purpose: The current study was conducted to investigate the potential pharmacokinetic and pharmacodynamic interactions between warfarin and puerarin which is the most abundant component in Pueraria lobata (Gegen). In vivo and ex vivo rat models were used to reveal the underlying mechanisms of such interactions. Methods: Apart from one control group, five groups of Sprague–Dawley rats were treated with warfarin, oral puerarin, oral puerarin with warfarin, intravenous puerarin, intravenous puerarin with warfarin. The treatment lasted for 5 consecutive days. Thereafter, the levels of warfarin, warfarin metabolites and puerarin in plasma of these rats were monitored and compared. The rCyps activity and expression in rat livers of different treatment groups were assessed. The prothrombin time was observed. The vitamin K epoxide reductase (VKOR) activity and expression in rat livers were evaluated. Thrombomodulin activity and expression in the rat lung and rat plasma were assessed. The soluble thrombomodulin (sTM) concentrations of different treatment groups were examined. Results: Intravenously administered puerarin altered the pharmacokinetics of warfarin significantly by shortening t 1/2, decreasing AUC 0–96 h and increasing the clearance of warfarin. Further mechanistic studies suggested that both oral and intravenous administration of puerarin significantly induced the activities and expressions of rCyp2b1, rCyp2c6 and rCyp1a1. In addition, co‐administration of puerarin reduced the prothrombin time of rat plasma by enhancing VKOR and inhibiting thrombomodulin. Conclusion: Puerarin increased warfarin metabolism and offset warfarin anticoagulation by inducing rCyps, upregulating VKOR and inhibiting thrombomodulin in rats. The clinical impact of such potential interactions warrants further verification. Copyright © 2016 John Wiley & Sons, Ltd.